ANALISIS TEKNO-EKONOMI PENDIRIAN PABRIK BIODESEL DARI BIJI NYAMPLUNG (Calophyllum inophyllum L.) - Yandra Arkeman, Dwi Setyaningsih dan Tika Ari Sanday TIP (Jurnal Teknologi Industri Pertanian, 2012)
World crises that occurred in the last decades indicated the scarcity of fuel. Fuel consumption is unbalanced with fuel production so it needs the development of alternative sources of energy. One of them is to use nyamplung seed. Nyamplung (Calophyllum inophyllum L.) is one of the biodiesel alternative raw material that has a large potential to be developed to overcome the problem of scarcity of fuel. The advantages of nyamplung as raw material for biodiesel are the dry seeds have high yield (approximately 70%) and its use does not compete with food purposes. The purpose of this study was to analyze techno-economic aspect of biodiesel industry establishment of nyamplung seed. Scope of research included techno-economic on the market and marketing aspects, technical and technological, management and organization, environmental, legal, valuation and commercialization, as well as financial aspects. This biodiesel industry is planned to be located in Banyuwangi, Indonesia with the selection criteria associated with using Analytical Hierarchy Process and the industrial capacity of 1000 liters per day with raw materials as much as 4500 kgs per day. After the assessment of all aspects, it can be concluded that the industry of biodiesel from nyamplung seed is feasible to be established.Keywords: techno-economic, nyamplung, biodiesel industry